Monoaurated vs. diaurated intermediates: causality or independence? - Anania, Mariarosa; Jašíková, Lucie; Zelenka, Jan; Shcherbachenko, Elena; Jašík, Juraj; Roithová, Jana (Chemical science, 2019)
Diaurated intermediates of gold-catalysed reactions have been a long-standing subject of debate. Although diaurated complexes were regarded as a drain of active monoaurated intermediates in catalytic cycles, they were also identified as the products of gold-gold cooperation in dual-activation reactions. This study shows investigation of intermediates in water addition to alkynes catalysed by [(IPr)Au(CH3CN)(BF4)]. Electrospray ionisation mass spectrometry (ESI-MS) allowed us to detect both monoaurated and diaurated complexes in this reaction. Infrared photodissociation spectra of the trapped complexes show that the structure of the intermediates corresponds to α-gold ketone intermediates protonated or aurated at the oxygen atom. Delayed reactant labelling experiments provided the half life of the intermediates in reaction of 1-phenylpropyne (∼7 min) and the kinetic isotope effects for hydrogen introduction to the carbon atom (KIE ∼ 4-6) and for the protodeauration (KIE ∼ 2). The results suggest that the ESI-MS detected monoaurated and diaurated complexes report on species with a very similar or the same kinetics in solution. Kinetic analysis of the overall reaction showed that the reaction rate is first-order dependent on the concentration of the gold catalyst. Finally, all results are consistent with the reaction mechanism proceeding via monoaurated neutral α-gold ketone intermediates only.